2,2′-Bithiophene as sensor tag for ligand-protein binding assays based on Förster resonance energy transfer - Behnam, Mira A. M.; Basché, Thomas; Klein, Christian D. (Analytical biochemistry, 2023)
Ligand-protein binding assays based on intrinsic protein fluorescence are straightforward, inexpensive methods to study ligand-protein interactions. However, their applicability is limited to ligands that can interfere with protein emission. In this Note, we describe the applicability of 2,2′-bithiophene as a FRET-based sensor tag, that can be incorporated into high-affinity ligands to generate target-specific compounds able to quench protein fluorescence upon binding. The generated ligands were assessed in different assay designs. Considerations to account for possible sources of interference with the assay readout are addressed, besides interpretation of the obtained results.
Gesehen am 17.01.2024